2015
DOI: 10.3389/fimmu.2015.00093
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Gene Expression in the Thymus: A Matter of Epigenetics, miRNA, and More?

Abstract: The induction of central tolerance in the course of T cell development crucially depends on promiscuous gene expression (pGE) in medullary thymic epithelial cells (mTECs). mTECs express a genome-wide variety of tissue-restricted antigens (TRAs), preventing the escape of autoreactive T cells to the periphery, and the development of severe autoimmunity. Most of our knowledge of how pGE is controlled comes from studies on the autoimmune regulator (Aire). Aire activates the expression of a large subset of TRAs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 74 publications
1
43
0
Order By: Relevance
“…Control of PGE may be more complex and may involve epigenetic mechanisms and posttranscriptional regulation involving miRNAs (5, 28, 33, 34). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of PGE may be more complex and may involve epigenetic mechanisms and posttranscriptional regulation involving miRNAs (5, 28, 33, 34). …”
Section: Introductionmentioning
confidence: 99%
“…Our group demonstrated for the first time that the Aire gene regulated the expression of miRNAs in mTECs (35). Additionally, miRNAs in the thymus were associated with T cell development, posttranscriptional regulation of the Aire mRNA and PGE, maintenance of the thymic architecture, and thymic cellularity (33, 34, 36, 37). …”
Section: Introductionmentioning
confidence: 99%
“…The expression of TRAs is in part under the control of the autoimmune regulator (Aire), but also controlled by the transcription factor Fez2f 56. Aire has also been implicated to be important for antigen transfer from mTECs to dendritic cells (DCs) as well as for regulation of the expression of mTEC specific miRNAs important for TRA expression and TEC maturation78. Antigen transfer from TECs to DCs and thymocytes as well as intercellular sharing of miRNA within the thymic microenvironment might be prerequisites for optimal thymic function.…”
mentioning
confidence: 99%
“…It has been shown that miRNAs play important roles in regulating cell death and proliferation during the process of aging [40]. Several studies have revealed that miRNAs are necessary in the maintenance and function of the TECs [36,[40][41][42]. However, whether miR-195a directly regulates TECs function remains unclear.…”
Section: Discussionmentioning
confidence: 99%